Effect of maximum stress intensity factor, loading mode, and temperature on corrosion fatigue cracking behavior of Inconel 617 in supercritical water. (January 2019) - Khan, Hasan Izhar; Zhang, Naiqiang; Xu, Weiqiao; Zhu, Zhongliang; Jiang, Dongfang; Xu, Hong
Highlights: Corrosion fatigue cracking behavior of Inconel 617 is evaluated. Fatigue crack growth rate increases with an increase in Kmax and temperature. Different loading waveforms have no obvious effect on fatigue crack growth rate. Abstract: Inconel 617 is a candidate material to be used as a structural material in ultra-supercritical power plants. In such an extreme corrosive medium environment, metallic materials are susceptible to corrosion fatigue. In the present study, the aim is to evaluate the effect of maximum stress intensity factor, loading mode and temperature on the corrosion fatigue cracking behavior of Inconel 617 in a deaerated (<10 ppb dissolved oxygen) supercritical water environment. Water pressure was kept constant at 25 MPa while its temperature was maintained at 600, 620 and 650 °C in the applied test conditions. For the selected parameters, microscopic investigations and detailed analysis affirmed corrosion-fatigue interaction to be leading factor for change in fatigue crack growth rate. The crack propagation mechanism for the selected parameters in the applied test conditions is further discussed.